Validation of an equine fitness tracker: ECG quality and arrhythmia detection. (25th March 2022) - ter Woort, Fe; Dubois, Guillaume; Tansley, Grace; Didier, Marie; Verdegaal, Elisabeth‐Lidwien; Franklin, Samantha; Van Erck‐Westergren, Emmanuelle
Summary: Background: Cardiac arrhythmias in exercising horses are the focus of much interest, both in terms of what is considered normal and potential associations with poor performance and sudden cardiac death. One barrier to performing large‐scale studies is the lack of an easily applicable device, to allow recording of large numbers of high‐quality exercising electrocardiograms (ECGs). The Equimetre TM is a new wearable device, which records a single lead ECG, among other parameters. Validation of such wearable devices is essential before further studies are undertaken. Objectives: To evaluate the quality of ECG using the Equimetre TM and compare arrhythmia detection during exercise with the reference Televet TM system. Study design: Prospective blinded clinical study. Methods: Simultaneous ECGs were recorded with both systems in 49 healthy horses during exercise. High‐intensity exercise (>40 km/h) was performed by 29 racehorses, and lower‐intensity exercise for the remainder of the racehorses and show jumpers. Tracings were excluded if >10% artefact was present (duration of artefact relative to duration of exercise). For included ECGs, the duration of artefact was recorded and compared. ECGs were evaluated using Kubios premium software. Arrhythmia detection (yes/no) and arrhythmia classification (sinus arrhythmia, narrow complex of similar morphology to the sinus complexes or wide complex with a different morphology) were compared using Cohen's Kappa coefficient. Results: Nine Televet TM ECGs and 3 Equimetre TM ECGs were excluded due to artefact >10%. Televet TM ECGs included significantly more artefact during exercise than Equimetre TM ECGs (5% vs. 0.25% P < .001). Arrhythmia analysis was performed on 38 horses' paired ECGs. The kappa coefficient was excellent for arrhythmia detection (K = 0.97) and arrhythmia classification (K = 0.93). Main limitations: Relatively low numbers of horses with arrhythmias (n = 21) were included. The ECG recordings only provided one lead, making arrhythmia classification challenging in some cases. Conclusions: The Equimetre device provides a reliable ECG for arrhythmia detection during exercise. This system may be useful clinically and for future large‐scale investigations into the occurrence and significance of exercising arrhythmias. Summarize: Background: Arrhythmia in sports horses is a focus of attention and has a strong and potential association with poor athletic performance and sudden cardiac death. One limitation of conducting large‐scale studies is the lack of an easily applicable device to record large numbers of high‐quality exercise electrocardiograms (ECGs). Equimeter is a new type of wearable device that records single‐lead electrocardiograms, among other parameters. Validation of such wearables is necessary before further research. Objectives: .To evaluate the quality of the Equimeter ECG and to compare the detection of arrhythmias during exercise with the Televet reference system. Study design: Prospective blinded study. Methods: Electrocardiograms were recorded in 49 healthy horses using both systems simultaneously during exercise. Among them, 29 racehorses performed high‐intensity exercise (>40km/h), while the rest of the racehorses and obstacle horses performed moderate‐to‐low‐intensity exercise. Tracking recordings were excluded if >10% artifacts (artifact duration relative to motion duration) were present. For included ECGs, the duration of the artifact was recorded and compared. Electrocardiograms were assessed using Kubios advanced software. Arrhythmias (presence/absence) and classification of arrhythmias (sinus arrhythmias, narrow complexes similar to sinus complexes, or broad complexes with different morphology) were detected using Cohen's Kappa coefficient. Results: Due to artifacts, 9 Televet ECGs, and 3 Equimetre ECGs were excluded. During exercise, the Televet system produced significantly more artifacts than the Equimetre system (5% vs 0.25%, P < 0.001). Cardiac arrhythmia analysis was performed on the electrocardiograms of 38 horses. Kappa correlation coefficient results were good: arrhythmia detection (K = 0.97) and arrhythmia classification (K = 0.93). Major limitation: The number of arrhythmic horses included was relatively small (n = 21). ECG recordings provide only 1 lead, making arrhythmia typing difficult in some cases. Conclusions: The Equimeter device provides a reliable ECG for the detection of arrhythmias during exercise. The system could be used for large‐scale studies on topics such as the occurrence and significance of equine exercise arrhythmias in the future.